Pitfalls of Nationalism in the Middle East and North Africa Region - Bendebka, Ramzi (Enviro Research Publishers, 2020)
Nationalism in the Middle East and North Africa (MENA) region is a fundamental issue. As long as this fundamental issue is not well discussed, any reforms in the regional system, including integration and state building, would be insufficient in alleviating the challenges faced by Arab nations as they attempt unity in the region. Any understanding of how and why MENA states make political choices towards stability and unity, necessitates the understanding of how they view themselves in terms of representing identity. The objective of this study is to investigate the transformation and the changing nationalism in the modern MENA region. For instance, Arab society has courted several ideologies from Arabism or Arab nationalism and Arab Islamic nationalism, among others. Ideologies do not exist in a vacuum. Therefore, it is necessary to investigate the context in which several ideologies interact with each other and affect nationalism in the MENA region. Although Arab nationalism continues to play an ideological role, what is its relation with Islam? Why Arab Islamic nationalism in the MENA region does not unite states or non-state groups like the cases of Iran and the Kurds? It is therefore useful for this article to illustrate firstly, the relation between Arab nationalism and Arab Islamic nationalism, secondly, the case of Iran nationalism and finally, the Kurds and their strive for a separate nationalism.